Vertebral column deformities in a freshwater catfish Mystus gulio - Marimuthu, K; Haniffa, M A; Muruganandam, M; Arockiaraj, A Jesu; Johnson, J Antony (Indian Journal of Fisheries, 2011)
The observed deformities in the vertebral column of two specimens of a cat fishspecies Mystus gulio caught from river Tambaraparani in Tamil Nadu are reported.Whereas the normal counts in the pre and post anal region are 12 and 23 thedeformed fishes had counts at the rate of 12 and 26, and 15 and 22 respectively